Does Systemic Risk in the Financial Sector Predict Future Economic Downturns? - Allen, Linda; Bali, Turan G.; Tang, Yi (Review of Financial Studies, 2012)
We derive a measure of aggregate systemic risk, designated CATFIN, that complements bank-specific systemic risk measures by forecasting macroeconomic downturns six months into the future using out-of-sample tests conducted with U.S., European, and Asian bank data. Consistent with bank “specialness,” the CATFIN of both large and small banks forecasts macroeconomic declines, whereas a similarly defined measure for both nonfinancial firms and simulated “fake banks” has no marginal predictive ability. High levels of systemic risk in the banking sector impact the macroeconomy through aggregate lending activity. A conditional asset pricing model shows that CATFIN is priced for financial and nonfinancial firms.